Management of thyroid disease in pregnancy – Room for improvement in the first trimester - Robinson, Helen (Obstet Med, 2016)
BACKGROUND: First-trimester care of maternal thyroid dysfunction has previously been shown to be poor. This study evaluates early management of thyroid dysfunction in pregnancy in Australia. METHODS: Patients reviewed by the Obstetric Medicine team for thyroid dysfunction from 1 January 2012 to 30 June 2013 were included. Data were collected on gestation at referral from the patient’s general practitioner to the antenatal clinic, information provided in the referral letter, thyroid function tests and thyroid medications. RESULTS: Eighty-five women were included in the study. At the time of general practitioner referral to antenatal services, 19% of women with preexisting thyroid disease had no thyroid function tested. Forty-three percent had an abnormal thyroid-stimulating hormone defined as being outside the laboratory-specific pregnancy reference range if available, or outside the level of 0.1–2.5 mIu/L in the first trimester, 0.2–3.0 mIu/L in the second trimester and 0.3–3.0 mIu/L in the third trimester. Only 21% of women increased their thyroxine dose prior to their first antenatal clinic review. CONCLUSION: This study highlights that a significant proportion of women with known thyroid disease either have untested thyroid function in the first trimester or a thyroid-stimulating hormone outside of levels recommended by guidelines.